2014
DOI: 10.1371/journal.ppat.1003973
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Membrane Anchor of Pestivirus Glycoprotein Erns, a Long Tilted Amphipathic Helix

Abstract: Erns is an essential virion glycoprotein with RNase activity that suppresses host cellular innate immune responses upon being partially secreted from the infected cells. Its unusual C-terminus plays multiple roles, as the amphiphilic helix acts as a membrane anchor, as a signal peptidase cleavage site, and as a retention/secretion signal. We analyzed the structure and membrane binding properties of this sequence to gain a better understanding of the underlying mechanisms. CD spectroscopy in different setups, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 84 publications
(130 reference statements)
0
69
0
Order By: Relevance
“…E rns contains an amphipathic helix domain of 61 residues for membrane binding instead of a transmembrane [12]. Although the current study revealed that the C-terminal helix domain of E rns plays a crucial role in the infectious particle formation, the helix domains from exchangeable apolipoproteins and CAMP have been shown to play similar roles in particle formation [10, 11].…”
Section: Discussionmentioning
confidence: 92%
“…E rns contains an amphipathic helix domain of 61 residues for membrane binding instead of a transmembrane [12]. Although the current study revealed that the C-terminal helix domain of E rns plays a crucial role in the infectious particle formation, the helix domains from exchangeable apolipoproteins and CAMP have been shown to play similar roles in particle formation [10, 11].…”
Section: Discussionmentioning
confidence: 92%
“…Within this segment, a stretch of 15 amino acids shows no exchange of N-bound protons with water. These residues have either no water contact indicating complete insertion into the membrane or are fixed in a very stable helix forming upon contact with the lipid bilayer so that the N-linked protons are trapped in a rigid structure (Aberle et al, 2014) (Fig. 7).…”
Section: E Rnsmentioning
confidence: 99%
“…Image was rendered with PyMOL using the structure deposited in the PDB database (4DVK) (PyMOL: The PyMOL Molecular Graphics System, Version 1.7.4 Schrödinger, LLC). (C) An MD simulation of the E rns membrane anchor taken fromAberle et al (2014).…”
mentioning
confidence: 99%
“…OCD is a powerful tool for studying the orientation of membrane-active peptides and protein segments in membranes (Lange et al, 2007;Bürck et al, 2008;Strandberg et al, 2008;Wadhwani et al, 2008Wadhwani et al, , 2012Wadhwani et al, , 2014Nolandt et al, 2009;Windisch et al, 2010;Heinzmann et al, 2011;Klein et al, 2012;Muhle-Goll et al, 2012;Steinbrecher et al, 2012;Aberle et al, 2014;Fanghänel et al, 2014). For α-helices, the OCD band at 208 nm can be used to estimate the helix tilt angle relative to the membrane normal (Wu et al, 1990).…”
Section: Orientation Of E5 In the Membrane By Ocdmentioning
confidence: 99%